Long-term field pH manipulation influence on microbial activity, water repellency and physical properties of soil - Fountouli Anastasia; Paton Graeme I.; Watson Christine A.; Walker Robin L.; Raffan Annette; Hallett Paul D. (Journal of Hydrology and Hydromechanics, 2024)
Studies across multiple soils find increasing pH decreases water repellency. In this study, water repellency and a range of other soil physical properties of bulk soils, aggregates and intact specimens were measured on a long-term pH field experiment on a single sandy loam soil under a ley-arable crop rotation, with soil pH adjustments occurring annually by adding FeSO4 or CaCO3, to lower or raise the pH, respectively. Crop impacts were investigated by comparing 3rd year grass-white clover to spring oats, at the beginning (May) and end (September) of the growing season to allow soil structure comparisons. As in previous research, increased CO2 microbial respiration (p<0.05) was found with increasing pH along the gradient, but in this study, we found only the aggregate and soil bulk density affected by soil pH. Soil-water contact angles differed between crops (p<0.05), as well as the repellency index of soil aggregates, however, there was no soil pH effect. Overall, differences in data were found to be a result of the various crops in the rotation rather than by soil pH, indicating only minor impacts on soil physical characteristics after > 55 years of chemical additions to amend soil pH.